Features of the Higher Nervous Activity and Psychic Processes of Students with Intellectual Deficiencies - Nabiev Ravshanjon Shavkatjon Ogli; Quchqorova Farida Erkin Qizi (Genius Journals, 2023)
This article describes the intellectual shortage of bo‘did it o‘readers back of higher nervous activity and psixik process features about the word is doing. A number of scientists by analysis of the results , causing mentioned
Keywords: Intellect; higher nervous activity; pixie jarayonliar